(untitled) (Bangladesh Journal of Medicine, 2021)
Background: Oxidative stress induced cancer cell formation. Gene polymorphism plays roles in carcinogen metabolism, antioxidant and DNA repairing pathway was susceptibility to oxidative stress. This study aim to determine the association between CAT-21 A/T polymorphism with breast cancer susceptibility. Methods: Case control study was conducted on 65 breast cancer patient and 65 healthy control group. The whole blood samples were isolated from 65 breast cancer patients in Haji Adam Malik General Hospital Medan and 65 healthy control group. The CAT-21A/T polymorphism was analyzed by PCR-RFLP procedure. PCR-RFLP product was electrophoresed and visualized in agarose 4%. Results:The AA CAT-21 genotype were lower in breast cancer (BC) than healthy control (HC) group (31/47.7% vs 40/61.5%), in the contrary AT+TT genotype was greater in BC than HC group (34/52.3% vs 25/38.5%) with (p=0.159, OR=1.755, CI=0.874–3.525). A allele CAT-21 were found lower in BC than HC group (89/68.5% vs 105/80.8%) then T allele were greater in BC than HC group (41/31.5% vs 25/19.2%) with (p=0.033, OR=1.935;CI=1.022-3.428). Conclusions: There was significant difference in allele distribution of CAT-21 A/T between case and control group but no in genotype distribution. In this population study showed that allele of CAT -21 A/T polymorphism could represent as a risk factor to breast cancer. Bangladesh J Medicine July 2021; 32(2) : 79-84